2014
DOI: 10.1128/aac.01532-13
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Isoniazid in Low-Birth-Weight and Premature Infants

Abstract: dIsoniazid (INH) is recommended for use as posttuberculosis exposure preventive therapy in children. However, no pharmacokinetic data are available for INH treatment in low-birth-weight (LBW) infants, who undergo substantial developmental and physiological changes. Our objectives in this study were to determine the pharmacokinetic parameters of INH at a dose of 10 mg/kg of body weight/day and to define its pharmacokinetics relative to the arylamine N-acetyltransferase-2 (NAT2) genotype. An intensive prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 25 publications
2
24
0
2
Order By: Relevance
“…Infant INH concentrations also compared well with other pediatric pharmacokinetic studies with similar 2-hour concentrations reported of 4.5, 5.6, and 3.9 to 8.6, following 10 to 15 mg/kg (7,27,38). The effect of acetylator status on INH exposures is not reported here (future work).…”
Section: Discussionsupporting
confidence: 64%
“…Infant INH concentrations also compared well with other pediatric pharmacokinetic studies with similar 2-hour concentrations reported of 4.5, 5.6, and 3.9 to 8.6, following 10 to 15 mg/kg (7,27,38). The effect of acetylator status on INH exposures is not reported here (future work).…”
Section: Discussionsupporting
confidence: 64%
“…Therefore, it was decided that further optimization of the dose regimen for isoniazid was not necessary. Even if the dosing for children aged 2–16 years seems to be adequate, this cannot be assumed to be true for younger children (age <2 years) as enzyme maturation needs to be taken into account for this group .…”
Section: Discussionmentioning
confidence: 99%
“…Due to reduced metabolism, NAT2 slow acetylators have reduced clearance and increased exposure to INH and hydrazine compared to rapid acetylators [63, 6670]. NAT2 slow acetylator profile (or two slow NAT2 alleles) has therefore been associated with an increased risk of hepatotoxicity/ liver injury/ hepatitis induced by anti-TB drug treatment as compared to rapid acetylators (and sometimes intermediates) in many studies [43–46, 7187].…”
Section: Pharmacogeneticsmentioning
confidence: 99%